PENGARUH CURRENT RATIO, RETURN ON ASSET, EARNING PER SHARE, DEBT TO EQUITY, ASSET TURNOVER DAN ARUS KAS OPERASIONAL TERHADAP RETURN SAHAM (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013â2015) - Lina Agustina, 13.05.52.0105; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyse the effect of the pengaruh current ratio, return on asset, earning per share, debt to equity, asset turnover and operating cash flow on stock returns empirical study of the campanies in the manufacturing sector which were listed in Indonesian Stock Exchange. The population in this study are all manufacturing companies listed in indonesia stock exchange in 2012-2014.Â The population of this research is 152 campanies in the manufacturing sector which were listed in Indonesian Stock Exchange. The sampling technique is purposive sampling, sampling obtained a sample of 46 companies. Data analysis technique used is multiple linear regression analysis. The results of this study show that each variable has a different effect, namely return on asset leave a positive and significant impact on stock return, current ratio negatively and significant on stock return, earning per share and asset turnover positive impact and no significant effect on stock return, while a debt to equity and cash flow operating activities negative impact and no significant effect on stock return. For further research should add other variables that affect stock return companies.Keywords: Current Ratio, Return On Asset, Earning Per Share, Debt To Equity, Asset Turnover, Cash Flow Operating Activities and Stock Return